Analysis Of Macroeconomic Indicators Of The Republic Of Uzbekistan - Shodmanova, Zubayda Ubaydullayevna; Ashurova Jasmina (Journal of Innovation in Education and Social Research, 2026)
This article analyzes the main macroeconomic indicators of the Republic of Uzbekistan for 2021–2025 - the dynamics of gross domestic product growth, inflation rate, foreign trade balance, development trends of industrial and service sectors. The study was based on official statistical data and scientific works of local and foreign economists. Based on the results of the analysis, it was proven that the national economy is developing towards sustainable growth, problems in the sectoral sector were identified, and practical proposals were developed to increase economic efficiency.